Factors Affecting Students’ Accessibility and Utilization of ICT in Home Economics Education in University of Calabar - Arikpo Iyam, Mary; Out Oka, Christiana (International Journal of Psychosocial Rehabilitation, 2020)
This study empirically focused on factors affecting students’ accessibility and utilization of ICT in home economics education at the University of Calabar. To achieve the aim of this study, two specific objectives, two research questions, and two hypotheses were formulated. The paper adopted a descriptive survey design. The population for the study was 223 home economics students from three academic sessions, of which 143 were sampled using the stratified sampling method. A structured 4-point rating scale questionnaire, which was duly validated by two experts in the field, was used to collect data from the study. Data generated were analyzed using simple percentages, while the two hypotheses were tested using Spearman’s Rank Correlation Coefficient analysis at a .05 level of significance. Findings showed that all eight items of the questionnaire were factors affecting students’ accessibility and utilization of ICT in home economics education at the University of Calabar. Based on the findings, it was recommended, among others, that both lecturers and students should provide a written report on how they have accessed and utilized computers and encourage students to share their experiences in class as well as publish the benefits of computers.